Comparison of the Interactions of Fibrinogen and Soluble Fibrin with Washed Rabbit Platelets Stimulated with ADP - Harfenist, Elizabeth J; Packham, Marian A; Mustard, J Fraser (Thrombosis and Haemostasis, 1985)
Because fibrin, formed at a site of vessel wall injury, is involved in the formation and stabilization of a platelet aggregate or thrombus, we have studied reactions of fibrin with rabbit platelets. Gly-Pro-Arg-Pro, an inhibitor of fibrin polymerization, was used to prepare soluble fibrin. Fibrin alone did not cause aggregation of washed platelets, but addition of ADP caused aggregation and deaggregation identical to those observed in the presence of fibrinogen. Specific binding of 125I-fibrin to ADP- stimulated platelets was similar to that of 125I-fibrinogen, but 125I-fibrin did not dissociate, even in the presence of high concentrations of apyrase. High non-specific binding of 125I-fibrin was observed that was not associated with aggregation. EDTA, prostaglandin E1 (PGE1) and creatine phosphate/creatine phos- phokinase prevented ADP-induced aggregation in the presence of fibrin and caused rapid deaggregation when added after ADP. They also inhibited 125I-fibrin binding when added before ADP, and EDTA or PGE1 caused partial dissociation of bound 125I-fibrin. In vivo, fibrin may bind to stimulated platelets, polymerize, form a gel, and interact with components of the plasma, the platelet aggregate, and the exposed subendothelium.
Keywords: Platelets; Fibrinogen; Fibrin; ADP